2014
DOI: 10.5964/pch.v3i2.89
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Body Shape Concern: A Challenge

Abstract: ResumoObjetivo: Apresentar, por meio de revisão de literatura, uma abordagem teórica sobre o constructo "imagem corporal" destacando a vertente da "preocupação com a forma corporal" e as propriedades psicométricas da escala Body Shape Questionnaire (BSQ). Método: Foi realizado um levantamento bibliográfico dos estudos publicados no período de 1987 a 2012 que estavam disponíveis na íntegra nas bases de dados Pubmed, Bireme e Scielo. A procura e seleção dos artigos foi realizada entre Janeiro e Março de 2013. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
2
0
1
Order By: Relevance
“…The global results observed indicate dimensions that are highly valued in the school context, seeming to indicate a high potential of these students who practice nautical modalities (without body contact) in the pursuit of academic tasks, a situation evidenced in this study as well. The same situation was found in the study by Silva et al (2014) in soccer practitioners (with body contact) in which athletes perceive the influence of sports practice on self-esteem and self-concept, and also on peer and interpersonal relationships, and that in general, sports practice influenced school performance. Still with reference to school performance, it was identified in the study by Maciel et al (2107) that this variable was never compromised and even increased in students practicing extra-curricular basketball sports (with body contact).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The global results observed indicate dimensions that are highly valued in the school context, seeming to indicate a high potential of these students who practice nautical modalities (without body contact) in the pursuit of academic tasks, a situation evidenced in this study as well. The same situation was found in the study by Silva et al (2014) in soccer practitioners (with body contact) in which athletes perceive the influence of sports practice on self-esteem and self-concept, and also on peer and interpersonal relationships, and that in general, sports practice influenced school performance. Still with reference to school performance, it was identified in the study by Maciel et al (2107) that this variable was never compromised and even increased in students practicing extra-curricular basketball sports (with body contact).…”
Section: Discussionsupporting
confidence: 77%
“…The practice of physical exercise is understood as a very good factor in satisfaction with body image. Even if it is not within the aesthetic standards stipulated by the media, the adolescent feels higher self-esteem due to the morphological changes caused by physical exercise (lean mass gain and fat mass loss), considering that the body fat is a neglected factor in our society (Silva et al, 2014). Batista et al (2016) states that the level of satisfaction with body image is more positive in individuals who are involved in sports activities, compared to those who are not.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier work, Silva et al. (2016) reported that scores on the Portuguese version of the BSQ achieved adequate fit among university women following the removal of two items (#26 and 32) related to assessment diagnostics for eating disorders rather than body concerns, as is consistent with other work among similar cultural groups (Silva et al., 2014). However, this reduced item pool potentially creates an ipso facto problem vis-à-vis invariance, if it is assumed that a 32-item model should be fitted for men.…”
Section: Methodssupporting
confidence: 67%
“…Studies examining sex differences among BSQ respondents (Amaral & Ferreira, 2017;Branco et al, 2006;Di Pietro & da Silveira, 2009;Laus et al, 2013) have typically found that men and boys obtain significantly lower BSQ scores than women and girls, leading researchers to conclude that women are more concerned with their body shape and weight than are men. However, such a conclusion may be unwarranted, given that BSQ items were originally designed to assess body concerns in women and not men (Silva et al, 2016;Silva, Dias, Pimenta, & Campos, 2014). That is, while any comparison of BSQ scores across sex presupposes that the measure functions similarly across these two groups (Slof-Op t'Landt et al, 2009), no prior research has established the sex invariance of this instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Esses são instrumentos denominados psicométricos, ou seja, construídos com base em métodos padronizados com a finalidade de medir conceitos abstratos, não mensurados diretamente (como, por exemplo, afetos, comportamentos e percepções) 6 . Porém, é importante destacar que a escolha do instrumento para a avaliação do bem-estar subjetivo deve estar elencada no contexto de aplicação e na adequação do instrumento escolhido para amostra nos diferentes contextos 7 .…”
Section: Introductionunclassified